A Case Report of a Post Cholecystectomy Patient with Anaemia, Jaundice and Splenomegaly - Paul, TK; Kabir, AL; Rahman, SS; Paul, N (Bangladesh Medical Journal, 2011)
DOI: 10.3329/bmj.v39i2.7041 Bangladesh Medical Journal 2010, 39(2) pp.60-61